50.6k views
5 votes
how do you do #3? if you can please take a picture or just explain the process, not just the answer. (i don’t need a super detailed explanation it’s just it was assigned as hw even tho my teacher didn’t teach it to us :/)

how do you do #3? if you can please take a picture or just explain the process, not-example-1

1 Answer

5 votes

Hello from MrBillDoesMath!

Answer:

z = 28 (y/x)

Discussion:

" z varies inversely with x and directly with y" translates into

z = k * (y/x) (*)

Substituting x = 2, y = 3, z = 42 in (*) gives

42 = k (3/2) => multiply both sides by 2/3

42 (2/3) = k (3/2)(2/3) => 42(2/3) = 28; (3/2)(2/3) = 1

28 = k

Conclusion:

z = 28 (y/x)

Thank you,

MrB

User Andy Friese
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.